From mother to child: orbitofrontal cortex gyrification and changes of drinking behaviour during adolescence. (24th April 2015) - Kühn, Simone; Witt, Charlotte; Banaschewski, Tobias; Barbot, Alexis; Barker, Gareth J.; Büchel, Christian; Conrod, Patricia J.; Flor, Herta; Garavan, Hugh; Ittermann, Bernd; Mann, Karl; Martinot, Jean‐Luc; et al.
Abstract: Adolescence is a common time for initiation of alcohol use and alcohol use disorders. Importantly, the neuro‐anatomical foundation for later alcohol‐related problems may already manifest pre‐natally, particularly due to smoking and alcohol consumption during pregnancy. In this context, cortical gyrification is an interesting marker of neuronal development but has not been investigated as a risk factor for adolescent alcohol use. On magnetic resonance imaging scans of 595 14‐year‐old adolescents from the IMAGEN sample, we computed whole‐brain mean curvature indices to predict change in alcohol‐related problems over the following 2 years. Change of alcohol use‐related problems was significantly predicted from mean curvature in left orbitofrontal cortex (OFC). Less gyrification of OFC was associated with an increase in alcohol use‐related problems over the next 2 years. Moreover, lower gyrification in left OFC was related to pre‐natal alcohol exposure, whereas maternal smoking during pregnancy had no effect. Current alcohol use‐related problems of the biological mother had no effect on offsprings' OFC gyrification or drinking behaviour. The data support the idea that alcohol consumption during pregnancy mediates the development of neuro‐anatomical phenotypes, which in turn constitute a risk factor for increasing problems due to alcohol consumption in a vulnerable stage of life. Maternal smoking during pregnancy or current maternal alcohol/nicotine consumption had no significant effect. The OFC mediates behaviours known to be disturbed in addiction, namely impulse control and reward processing. The results stress the importance of pre‐natal alcohol exposure for later increases in alcohol use‐related problems, mediated by structural brain characteristics. Abstract : Adolescence is a common time for initiation of alcohol. The neuroanatomical foundation for later alcohol‐related problems may already manifest prenatally, particularly due to alcohol consumption during pregnancy.The present data support the idea that alcohol consumption during pregnancy mediates the development of neuroanatomical phenotypes, which in turn constitute a risk factor for increasing problems due to alcohol consumption in adolescence. The results stress the importance of prenatal alcohol exposure for later increases in alcohol‐use‐related problems, mediated by structural brain characteristics.